Editorial Vol9 no1 - Irene Stevens (Scottish Journal of Residential Child Care)
This year sees the tenth anniversary of SIRCC. Over the past ten years, there have been many changes in residential child care. This is, however, the defining feature of residential child care in Scotland. My first job in residential child care in Glasgow was in a large residential house in the South Side of Glasgow. The house was a large sandstone property and we had over 20 children in the unit. The age range went from 8 months old up to 18 years old. All bedrooms were shared, with 4-5 beds in each room. I was a 'houseparent' and the 'matron' lived onsite in a small bungalow in the garden. There were 3-4 staff on a typical shift. It sounds very alien nowadays but that's the way it was.